ΜΑΡΙΑ ΧΑΤΖΗΚΥΡΙΑΚΙΔΟΥ, Η Ιταλία του Νίκου Εγγονόπουλου - Χατζηκυριακίδου Μαρία (Σύγκριση/Comparaison/Comparison, 2022)
The Italy of Nikos Eggonopoulos The presence of the Italian culture is reflected in all kinds of art with which the diverse representative of Greek surrealism Nikos Eggonopoulos dealt. «Although, […], the French fed my childhood dreams with Italy and Spain, I [only] loved Italy, and then got to know it in person» he wrote to his later wife, underlining the theoretical and experiential stimuli he received from the other side of the Adriatic coast. From the brush to the pen and vice versa, through reflections and patterns, the Italian landscape, the visual arts, the historical and literary reality and, of course, the monuments of Italy «rest his soul» and exert, as he states, a «deep and invincible» charm for him. But beyond the observations and critical thoughts about Italy as a historical and cultural entity, the Italian culture is part of the artistic ecosystem created by Eggonopoulos. He combines, seemingly incongruously, the painters and poets of Italy by placing them next to ordinary people or Greek deities while, conversely, Greek poets are depicted in his paintings with Venetian masks and renaissance attire or are described in his poems wandering in the streets of Venice. In this way he achieves multiple connections between the arts and the spaces, creating mixed forms and approaches that seem to have a common denominator: the answer to the question that concerns the origins of the Greek identity. Although in his time such a thing was treated as heretical, for Eggonopoulos these effects not only do not alter but, on the contrary, renew the cultural creation, enhancing the uniqueness, the dynamics and the universality of Greek culture.